Around the world in 500 years: Inter‐regional spread of alien species over recent centuries. Issue 8 (7th June 2021) - Seebens, Hanno; Blackburn, Tim M.; Hulme, Philip E.; van Kleunen, Mark; Liebhold, Andrew M.; Orlova‐Bienkowskaja, Marina; Pyšek, Petr; Schindler, Stefan; Essl, Franz
Abstract: Aim: The number of alien species has been increasing for centuries world‐wide, but temporal changes in the dynamics of their inter‐regional spread remain unclear. Here, we analyse changes in the rate and extent of inter‐regional spread of alien species over time and how these dynamics vary among major taxonomic groups. Location: Global. Time period: 1500–2010. Major taxa studied: Vascular plants, mammals, birds, fishes, arthropods and other invertebrates. Methods: Our analysis is based on the Alien Species First Record Database, which comprises >60, 000 entries describing the year when an alien species was first recorded in a region (mostly countries and large islands) where it later established as an alien species. Based on the number and distribution of first records, we calculated metrics of spread between regions, which we termed "inter‐regional spread", and conducted statistical analyses to assess variations over time and across taxonomic groups. Results: Almost all (>90%) species introduced before 1700 are found in more than one region today. Inter‐regional spread often took centuries and is ongoing for many species. The intensity of inter‐regional spread increased over time, with particularly steep increases after 1800. Rates of spread peaked for plants in the late 19th century, for birds and invertebrates in the late 20th century, and remained largely constant for mammals and fishes. Inter‐regional spread for individual species showed hump‐shaped temporal patterns, with the highest rates of spread at intermediate alien range sizes. Approximately 50% of widespread species showed signs of declines in spread rates. Main conclusions: Our results show that, although rates of spread have declined for many widespread species, for entire taxonomic groups they have tended to increase continuously over time. The large numbers of alien species that are currently observed in only a single region are anticipated to be found in many other regions in the future.